OCCUPATIONAL HEALTH AND SAFETY AT WORK WITH TECHNICAL MATERIALS - HODIS, Zdenek; VYBIRAL, Petr (Journal of Technology and Information Education, 2012)
The article discussed the principles of safety when working with technical materials - metal, wood and plastics. Occupational health and safety is an important area of teacher education in technical education and information - PedF MU Brno. Basic skills with which students learn are able be used in teaching in elementary schools. Mastered the principles of occupational health and safety contribute to the improvement of teaching.
Keywords: OHS; Technical Materials; Education